Working Capital, Financing Constraints and Firm Financial Performance in GCC Countries - Murthy, Sree Rama (Information Management and Business Review, 2015)
This paper looks at the impact of level of working capital on a firm’s financial performance of 153 large manufacturing firms operating in the six Gulf Cooperation Council Countries (GCC).Three hypotheses being tested in the paper are that working capital levels and inventory levels have a negative impact on corporate financial performance, have a positive impact on corporate financial performance, or that there is no empirically provable relationship between working capital and inventory and financial performance. A number of control variables including firm size, gross margins, and age of the firm are used in the regression analysis, as financial performance is not purely dependent on working capital and inventory levels. Pre-tax return on assets (ROA-profit before tax divided by total assets) is used to measure corporate financial performance. Performance is strongly influenced by levels of accounts receivables; however inventory levels and payables have no impact on performance.